Associations Between Covid-19-Related Threat, Stress, and Smoking in UK Adults Aged Under- and Over-30. (11th August 2022) - Walker, Lucy; Cordero, Maria I.; McChesney, Gillian; Gee, Ivan; Grogan, Sarah
It has been suggested that smoking and age are associated with higher vulnerability to Covid-19. While threat of Covid-19 may reduce or stop smoking, increased stress due to lockdown could increase smoking behaviour. This study aimed to investigate changes in smoking behaviour in relation to age, Covid-19-related threat and subjective perceived stress during the UK lockdown. A cross-sectional study was performed. Online adverts were used to recruit UK residents who smoked combustible tobacco any time from January 2020. A questionnaire measured demographic information, smoking behaviour pre- and during-lockdown, perceived subjective stress (PSS), and Covid-19 related threat. Data were collected from a total of 145 participants (58% women, 39% men, 3% non-binary; mean age: 26 years, SD = 7.7), during UK lockdown between 22nd May and 22nd June 2020. Independent of stress and Covid-19-related threat, smoking was reduced in those aged less than 30 years. In participants aged 30 and above, increases in smoking behaviour were associated with higher PSS. The results highlight the relevance of the different stages of life on the relationship between stress, threat, and smoking behaviour. Greater emphasis should be placed on stress reduction for adult smokers aged 30 and above to enable smoking cessation.